Bibliometric and visualisation analyses of gastric ulcer knowledge areas and emerging trends, 2004–2024 - Liu, Zijian; Liu, Yi; Li, Yang; Sun, Yuyan; Song, Xiaoxiang; Chen, Lu; Zhou, Dan (Frontiers in Medicine, 2025)
BackgroundGastric ulcers are a form of peptic ulcers that present as ruptures of the mucosal lining of the stomach or the proximal intestinal lining extending beyond the muscularis mucosae, and Helicobacter pylori infection is one of the main causative factors of gastric ulcers. However, the growing incidence of Helicobacter pylori drug resistance and the emergence of specialised ulcers has necessitated continued research on gastric ulcers. This study surveyed global gastric ulcer research over the past two decades with the aim of identifying the major findings and emerging trends in the field.MethodsBibliometric analysis was performed using the search terms ‘Gastric ulcer’, ‘Gastric ulcer disease’, ‘Gastrohelcoma’, and ‘Stomach ulcers’. Data were extracted from the Web of Science Core Database (WoSCC) and visualised using CiteSpace software.ResultsThe Journal of Gastroenterology had the most cited papers. The largest number of papers was from the United States. The most frequently cited keywords were ‘Helicobacter pylori’, ‘peptic ulcer’, and ‘gastric ulcer’.ConclusionThe field of gastric ulcer research is rapidly expanding, and the existing research is focused on preventing the occurrence of gastric ulcers, exploring the pathogenesis of gastric ulcers, and identifying new methods of treating gastric ulcers.